Biological testing of titanium-containing implants with noble metal coatings in an in vivo experiment - A. A. Zheravin; S. I. Dorovskikh; E. S. Vikulova; T. V. Basova; M. B. Vasileva; Ya. L. Rusakova; N. B. Morozova (Сибирский онкологический журнал)
The aim of study is to conduct in vivo biological testing of titanium nickelide samples modifed with Ag/Pt or AuAg/Pt flm heterostructures in comparison with the bare carrier.Material and Methods. Titanium nickelide plates modifed with flm heterostructures made of noble metals and the laboratory mini-pigs used for in vivo tests were the objects of the study. To form flm structures on titanium nickelide samples, the physical gasphase deposition methods: ion plasma deposition (IPD) and thermal (PVD) sputtering were used. The Ag/ Pt or AuAg/Pt heterostructures were characterized by X-ray diffraction and scanning microscopy methods.Results. The biocompatibility of implants before (TiNi, control) and after (Ag/Pt/TiNi and AuAg/Pt/TiNi) modifcation with flm heterostructures was tested in in-vivo experiments on a laboratory animal (mini-pig). General toxic reactions of the body to the injected samples were absent. A comparative macroscopic and histological analysis of the condition of peri-implant tissues after 39 days of implantation was performed. The connective tissue capsule around the TiNi sample revealed the presence of a certain number of lymphocytes, eosinophils and macrophages, but these indicators decrease in the order of TiNi > AuAg/Pt/TiNi > Ag/Pt/TiNi.Conclusion. The positive effect of modifying the titanium nickelide surfaces with noble metal heterostructures on the biocompatibility of metal implants was demonstrated in an in vivo experiment.